QRICH1 variants in Ververi-Brady syndrome-delineation of the genotypic and phenotypic spectrum - Foehrenbach, Melanie; Jamra, Rami Abou; Borkhardt, Arndt; Brozou, Triantafyllia; Muschke, Petra; Popp, Bernt; Rey, Linda K.; Schaper, Joerg; Surowy, Harald; Zenker, Martin; Zweier, Christiane; Wieczorek, Dagmar; et al. (Clinical Genetics, 2020)
Ververi-Brady syndrome (VBS, # 617982) is a rare developmental disorder, and loss-of-function variants in QRICH1 were implicated in its etiology. Furthermore, a recognizable phenotype was proposed comprising delayed speech, learning difficulties and dysmorphic signs. Here, we present four unrelated individuals with one known nonsense variant (c.1954C > T; p.[Arg652*]) and three novel de novo QRICH1 variants, respectively. These included two frameshift mutations (c.832_833del; p.(Ser278Leufs*25), c.1812_1813delTG; p.(Glu605Glyfs*25)) and interestingly one missense mutation (c.2207G > A; p.[Ser736Asn]), expanding the mutational spectrum. Enlargement of the cohort by these four individuals contributes to the delineation of the VBS phenotype and suggests expressive speech delay, moderate motor delay, learning difficulties/mild ID, mild microcephaly, short stature and notable social behavior deficits as clinical hallmarks. In addition, one patient presented with nephroblastoma. The possible involvement of QRICH1 in pediatric cancer assumes careful surveillance a key priority for outcome of these patients. Further research and enlargement of cohorts are warranted to learn about the genetic architecture and the phenotypic spectrum in more detail.
CRIS-Team WoS Importer:2020-11-27